2000
DOI: 10.1161/01.hyp.36.6.1105
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Renal and Cardiac Effects of Vasopeptidase Inhibition With S21402 in Heart Failure

Abstract: Abstract-S21402 is a vasopeptidase inhibitor that simultaneously inhibits neutral endopeptidase (NEP) and angiotensinconverting enzyme (ACE). This study determined whether chronic treatment with S21402 produced different effects on sodium and water excretion, hormonal parameters, and cardiovascular structure compared with selective inhibition of ACE and NEP in a rat model of myocardial infarction-induced congestive heart failure (CHF). CHF rats received the vasopeptidase inhibitor (S21402, 100 mg ⅐ kg), or veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…These results are in line with some reports that demonstrated a greater natriuretic response of VPI in experimental CHF (9,20,32) compared with other conventional agents, such as ACE inhibitors. Administration of OMP into dogs with experimental heart failure induced by ventricular pacing pro- Fig.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with some reports that demonstrated a greater natriuretic response of VPI in experimental CHF (9,20,32) compared with other conventional agents, such as ACE inhibitors. Administration of OMP into dogs with experimental heart failure induced by ventricular pacing pro- Fig.…”
Section: Discussionsupporting
confidence: 92%
“…23 Our results are consistent with the previous findings 33 reporting that ACE inhibitors did not improve fractional LV shortening but attenuated myocardial hypertrophy and remodeling in this experimental model. 34,35 A new pharmacological mechanism of action for ACE inhibitors has recently been proposed, based on the observations that ACE also degradates Ang- (1-7). 36, 37 Ferrario's group found a significant increase in ACE2 mRNA levels after AT1-blockade for 4 weeks in rats after myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lung weight of the treated rats was not reversed to the normal level, chronic NEP inhibition appears to have a beneficial effect on pulmonary congestion caused by CHF. Burrell et al (2000) reported that S21402, a vasopeptidase inhibitor, may offer several advantages, such as enhanced sodium and water excretion and relief of pulmonary congestion in rats with CHF. Considering these observations, we suggest that sampatrilat prevented worsening of the symptoms of CHF, at least in part, due to chronic inhibition of NEP activity.…”
Section: Discussionmentioning
confidence: 99%